Let $f:A \to B$ and $C,D\subset A$ then we have the following properties:

$ \space i)\space f(C\cup D)=f(C)\cup f(D)$

$ii)\space f(C\cap D)=f(C)\cap f(D)$

I tried to prove the first property with a direct proof, and the second property with an element-wise proof.

Proof of $i)$

$f(C\cup D)=\{f(x)\in B:x\in C\cup D\}$ (by the definition of a functions's image)

$\space \space \space \space \space \space\space \space \space \space \space \space \space \space \space \space =\{f(x)\in B:x\in C \text{ or } x\in D\}$ ( just writing the set's property in words )

$ \space \space \space \space \space \space\space \space \space \space \space \space \space \space \space \space =\{f(x)\in B:x\in C \}\cup \{f(x)\in B:x\in D\}$ (by the definition of a union )

$\space \space \space \space \space \space\space \space \space \space \space \space \space \space \space \space = f(C)\cup f(D)$ (again by the definition of a functions image)

Proof of $ii)$

Let $f(x)\in f(C\cap D)$, then $x\in C\cap D$ hence $x$ maps to both $f(C)$ and $f(D)$, so $f(x)\in f(C)\cap f(D)$. Conversely, let $f(x)\in f(C)\cap f(D)$ then $x\in C$ and $x\in D$, and therefore $x$ maps to $f(C\cap D)$, hence $f(x)\in f(C \cap D)$. Since we have shown that $f(C \cap D) \subset f(C)\cap f(D)$ and that $f(C)\cap f(D) \subset f(C \cap D) $, we have shown that $ f(C\cap D)=f(C)\cap f(D)$.

I am not sure if the second proof is sufficient. I feel more confident with the first proof. If you could please give my some constructive feedback. Thank you for your time.


The second proof is wrong:

Take $C=\{c\}$ and $D=\{d\}$, $c\neq d$ and suppose that $f(c)=f(d)=y$ so we have $$f(C\cap D)=\emptyset\neq \{y\}=f(C)\cap f(D)$$

The mistake in your proof is: "Conversely, let $f(x)\in f(C)\cap f(D)$ then..." and you should correct this by: let $y\in f(C)\cap f(D)$ then there's $c\in C$ and $d\in D$ such that $f(c)=f(d)=y$ so in other word the preimage of $y$ is not necessary unique.

  • $\begingroup$ I see the light! Thanks I see the clearly what I did wrong. $\endgroup$ – JimmyJackson Jul 4 '13 at 9:04
  • $\begingroup$ You're welcome. $\endgroup$ – user63181 Jul 4 '13 at 9:40
  • $\begingroup$ Nice catch (of the mistake)! $\endgroup$ – Namaste May 26 '14 at 15:43

This is very elementary but I believe it works for 2. I f we assume $$X=\{a,b\},~~Y=\{c\}$$ and $A_1=\{a\},~~A_2=\{b\}$. If we define $f:X\to Y$ to be constant such that $f(a)=f(b)=c$, so you can easily seen that $f(A_1\cap A_2)=f(\emptyset)=\emptyset$ but $$f(A_1)\cap f(A_2)=\{c\}$$


Your first proof looks great. Your second proof is missing something though (because, in fact, the claim isn't true), since the $x$'s might not match. That is, we only know that: $$ y \in f(C) \text{ and } y\in f(D) \implies \exists x_1\in C \text{ such that } f(x_1)=y \text{ and } \exists x_2\in D \text{ such that } f(x_2)=y $$ In general, $f(C \cap D) \subseteq f(C) \cap f(D)$. To get equality, you must additionally require that $f$ be injective. This allows you to infer that: $$ f(x_1)=y=f(x_2) \implies x_1=x_2 \implies x_1 \in C \cap D \implies y=f(x_1) \in f(C \cap D) $$

  • $\begingroup$ So, without assuming that $f$ is injective we cannot prove property two right? $\endgroup$ – JimmyJackson Jul 4 '13 at 8:59
  • $\begingroup$ @JimmyJackson Yes, that's correct. $\endgroup$ – Adriano Jul 4 '13 at 15:55

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.